Vernacular Architecture Reinterpretation as a Sustainability Strategy: (Case: La Cove Beach Resto & Bar, Kupang City) - Sera, Novenrius Kornelius; Jeraman, Pilipus; Lake, Reginaldo Christophori; Kalli, Januaris G. (RUAS, 2026)
This study analyzes the reinterpretation of vernacular architecture as a sustainability strategy at La Cove Beach Resto & Bar on Lasiana Beach, Kupang City. The research focuses on the use of bamboo as the primary material, the application of passive coastal climate strategies, and the transformation of local cultural symbols into contemporary architectural forms. The method used is descriptive-qualitative with a case study approach through field observations, in-depth interviews, visual documentation, and a literature review. The findings reveal that La Cove employs a five-layer bamboo roof system that functions as thermal insulation, as well as hybrid bamboo-concrete columns that enhance structural capacity and resilience to the coastal environment. Furthermore, the reinterpretation of the “Bula Molik” from Rote culture demonstrates that local identity is not merely presented symbolically but also contributes to the building’s functional performance, particularly regarding rainwater runoff and shading. The research findings affirm that vernacular architecture can be productively reinterpreted within large-scale commercial typologies, offering design references for the development of sustainable coastal tourism in Eastern Indonesia.